The Concept of Information Needs in the Context of Children’s Nursing - Harley, Sarah (2009)
Aim: To examine the concept of information needs in the context of children’s nursing so as to bring the concept closer to its use in research and practice. Methods: A critical review using elements of concept analysis methodology to evaluate literature. Through identification of key associated concepts, a model was developed to represent the interactions involved in children’s information needs, recognition of these needs and effective information provision to meet them. Key words: Child* (or adolescent or young person or teenager), information needs, information, patient education and concept. Findings: Key elements of the concept ‘information needs’ were identified and used to develop a model to represent the interactions involved. The key elements identified are: a trigger leading to information needs; a resulting deficit in knowledge; information needed as a coping mechanism and for decision making, informed consent, participation, partnership, adherence and compliance with treatment; information seeking behaviour; communication within a tripartite relationship of child, parent and health professional in which information needs are recognised and met; the need for information to be developmentally appropriate and engaging; and new information needs developing from more in-depth knowledge. The use of the model to identify barriers to identifying and meeting the information needs of children. Key barriers identified were: the health professional not recognising the child’s information needs; information not being developmentally appropriate or engaging, information provision being inadequate in content; lack of signposting to sources of information; parents withholding information and too much information being given, which overwhelms the child.